ADIPS 2020 guideline for pre‐existing diabetes and pregnancy. (16th November 2020) - Rudland, Victoria L.; Price, Sarah A.L.; Hughes, Ruth; Barrett, Helen L.; Lagstrom, Janet; Porter, Cynthia; Britten, Fiona L.; Glastras, Sarah; Fulcher, Ian; Wein, Peter; Simmons, David; McIntyre, H. David; et al.
Abstract : This is the full version of the Australasian Diabetes in Pregnancy Society (ADIPS) 2020 guideline for pre‐existing diabetes and pregnancy. The guideline encompasses the management of women with pre‐existing type 1 diabetes and type 2 diabetes in relation to pregnancy, including preconception, antepartum, intrapartum and postpartum care. The management of women with monogenic diabetes or cystic fibrosis‐related diabetes in relation to pregnancy is also discussed.